Metal Organic Frameworks: Synthesis and Application - Victoria F. Samanidou; Eleni A. Deliyanni (Molecules, 2020)
The concept of metal−organic frameworks (MOFs) was first introduced in 1990; nowadays they are among the most promising novel materials [...]